Pemikiran Ibnu Rusyd Tentang Etika Pendidikan dan Relevansinya di Era Milenial - Multazam; Ikhsan, Arief Maulana; Ramadhan, Muhammad Fadli (DIMAR: Jurnal Pendidikan Islam, 2023)
The research aims to describe the historical thinking of the ancient philosopher Ibn Rushd regarding education, then explain the relevance of educational thought according to Ibn Rushd to Islamic education in the millennial era. Researchers used the library research method in compiling this article. Then the researcher collects data sources through manuscript literature, journals, books, and articles that are related to the discussion of this research. While the results of the research show that Ibnu Rushd has thoughts and ideas about education, that education is an applicable matter that needs to be supported by the right model too, so that its implementation is always in accordance with its theoretical implementation, with the aim of providing an accurate understanding so that it can be realized in the right actions . Ibn Rushd's view of education that is structured in terms of goals, directed curriculum, appropriate learning methods, and qualified educators are important factors in determining the success of education. Therefore, Ibn Rushd's ideas can be used as an important guide in the development of education.